Investigation of Parameters of Fused Deposition Modelling 3D Prints with Compression Properties - Dereje Berihun Sitotaw; Dominik Marcel Muenks; Yordan Kostadinov Kyosev; Abera Kechi Kabish (Advances in Materials Science and Engineering)
Three-dimensional (3D) printing has been attracting a great deal of attention in recent years in many application fields, for example, in the aerospace, construction, industry, art, education, protection, security, and medical fields. Printing methods, materials, and parameters influence the performance quality and determine the application sector of 3D prints. In this study, the print parameters are used as independent variables to investigate the compression strength of 3D printed cubes/cubes. The prints were produced by considering infill type, infill percentages, vertical wall, horizontal contours, and dimensions of items as the product parameters. The different printed samples were subjected to atmospheric conditions for 24 hours at (20 ± 1)°C temperature and (65 ± 2)% relative humidity. The samples were then subjected to a cyclic compression test with an indentation depth of 5 mm. The compression force to the planned displacement was measured. As seen from the results, the print parameters investigated in this research significantly influence the compression force and determine the performance of 3D prints according to the application sector. Although all parameters significantly influence the compression force of 3D prints, the magnitude and level of performance are different. Vertical walls relatively withstand high compression force while filling type gives soft and weak products with a relatively low mass. However, the choice of different pressure parameters can influence the compressive strength. With this knowledge, it will be possible in the future to print human soft tissues with a specific compressive strength using the FDM printing process.